Providing AIDS awareness education through village based women’s organization - Hashima-E-Nasreen; Chowdhury, Mushtaque; Ahmed, Syed Masud; Bhuiya, Abbas; Rana, AKM Masud (BRAC Research and Evaluation Division (RED), 2020)
Objectives: This study aimed to assess the effectiveness of a basic AIDS education module delivered through grassroot NGO network in rural Matlab, Bangladesh. It also explored the level of dissemination of knowledge gained by the BRAC members to their spouses and neighbours. Methods: Some basics of AIDS awareness education was provided to the local BRAC staff, shasthya shebika (village health workers) and village women through a one-day training workshop, village organization meetings and campaign. Two surveys, one before intervention (baseline) and the another after intervention were carried out in 10 villages of Matlab RDP area where BRAC is working either alone or jointly with ICDDR,B. A total of 788 BRAC members, their husbands and neighbours were surveyed randomly using a pretested structured questionnaire covering sociodernographic information, respondents' knowledge on what HIV/AIDS is, its transmission, facts and myths of HIV/AIDS, prevention and high risk behaviour/population. Pre- and post intervention findings were compared. Appropriate statistical tests were done where needed. Results: The analysis showed significant improvement in knowledge of BRAC members following intervention. This improvement was not seen in case of neighbours and husbands. The dissemination of knowledge from the BRAC members to their neighbours and husbands was found to be very poor. Conclusion: Findings of this study would be helpful for the policymakers in formulating low-cost strategies for effective IEC on AIDS through grassroot NGO network in rural Bangladesh.